PENINGKATAN HASIL BELAJAR IPA MATERI DAUR HIDUP HEWAN DENGAN MENGGUNAKAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS IV SDN NO. 200107 PADANGSIDIMPUAN - Sabri Nur Indah Sabri; Lili Nur Indah Sari; Ninda Hartini Dalimunthe (FORUM PAEDAGOGIK, 2022)
This study aims to solve the research problem, namely whether there is an increase in Science Learning Outcomes of Animal Life Cycle Materials by Using the Student Team Achievement Division (STAD) Model for Class IV Students at SDN No. 20107 Padangsidimpuan, North Padangsidimpuan District, Padangsidimpuan City Regency. The research design used the classroom action research method which contained two cycles. The subjects of this study were students in class IV SDN No. 200107 Padangsidimpuan. Class IV students totaled 20 people. Based on the results of the analysis of the average science value in the Animal Life Cycle material before using the Student Team Achievement Division (STAD) learning model, an average of 67.75 was in the "Enough" category. After using the Student Team Achievement Division (STAD) learning model, the average in the first cycle was 72.5 in the "High" category, and in the second cycle the average score was 83 in the "Very High" category. From the comparison of the learning outcomes of fourth graders at SD No. 20107 Padangsidimpuan, North Padangsidimpuan District, Padangsidimpuan City Regency, in the first cycle it was 40% and in the second cycle it was 95%. The results showed that the application of the Student Team Achievement Division (STAD) learning model could improve science learning outcomes for Animal Life Cycle material.